Fourier Transform EPR Spectroscopy of Trityl Radicals for Multifunctional Assessment of Chemical Microenvironment1. (2nd February 2014) - Bobko, Andrey A.; Dhimitruka, Ilirian; Zweier, Jay L.; Khramtsov, Valery V.
Abstract Pulse techniques in electron paramagnetic resonance (EPR) allow for a reduction in measurement times and increase in sensitivity but require the synthesis of paramagnetic probes with long relaxation times. Here it is shown that the recently synthesized phosphonated trityl radical possesses long relaxation times that are sensitive to probe the microenvironment, such as oxygenation and acidity of an aqueous solution. In principle, application of Fourier transform EPR (FT‐EPR) spectroscopy makes it possible to acquire the entire EPR spectrum of the trityl probe and assess these microenvironmental parameters within a few microseconds. The performed analysis of the FT‐EPR spectra takes into consideration oxygen‐, proton‐, buffer‐, and concentration‐induced contributions to the spectral shape, therefore enabling quantitative and discriminative assessment of pH, pO2, and concentrations of the probe and inorganic phosphate.